Från tre världar till många: Tankar om en berättandets etnografi - Palmenfelt, Ulf (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
During the last decades the interest in narratives has been increasing within several academic disciplines. Although folklorists have analyzed narratives since the days of the Grimm brothers, we still can use some of the aspects put forward by literature scholars, oral historians, social psychologists, and discourse analysts. Our folkloristic expertise, as I see it, lies in promoting the central role of the fieldwork, in the well-developed methods for meticulous text analyses, and in our focus on the cultural aspects of human life. The three-partite model suggested by Katharine Young gains analytical strength from its ability to join text analysis with performance analysis. In my article, I suggest that Young’s model could be enlarged to comprise also geographical, chronological, and emotional worlds, as well as worlds defined by actors and deeds. Another suggestion is to regard each single episode in a life history narrative as located in a taleworld of its own, the narrator assuming the role of a filmmaker, taking his audience abruptly from one cut to the next. Such an approach, to my mind, makes it easier to separate emotions and attitudes embedded at different levels in the narrative and the narrative situation.